Subsidies to technology adoption when firms' information is endogenous - Luca Colombo; Gianluca Femminis; Alessandro Pavan (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2023)
How should firms be incentivized to adopt new technologies when the technical merits and spillovers of such technologies are uncertain? We show that, when information is dispersed but exogenous, efficiency can be induced with simple (constant) subsidies. When, instead, firms must also be incentivized to collect information efficiently, subsidies must be conditioned on the ex-post profitability of the new technology and, when the cost of information acquisition is unknown to the planner, on the aggregate investment in the new technology. The optimal policy has a Pigou's flavor but accounts for the non-observability of firms' acquisition and usage of information.
Keywords: D21; D62; D83; 330; endogenous information; investment spillovers; optimal policy; welfare